1994
DOI: 10.1021/bi00177a015
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Localization of Diacylglycerol in the Insect Lipoprotein Lipophorin. A 13C-NMR Study

Abstract: In order to probe the organization of diacylglycerol (DG) in lipophorin, 13C-enriched lipophorin was prepared for NMR investigations. We obtained 13C-enriched lipophorin labeled exclusively in DG by feeding insects tobacco leaves coated with [1-13C]palmitic acid or [1-13C]oleic acid. Lipophorins enriched up to 5% with a [13C]fatty acid were obtained by this procedure. NMR studies of the isolated lipophorin DG showed that palmitic acid accumulates almost entirely (> 90%) in the sn-1 position. Oleic acid was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…A signal at d 179.8 in the 13 C NMR spectrum indicated the presence of acidic carbonyl function. Based on these data and those reported by Kawahara et al (2000) and Soulages et al (1994), we concluded that the isolated antifouling compound was 2-hydroxymyristic acid (HAB) (Fig. 1).…”
Section: Identification Of Antifouling Compoundssupporting
confidence: 70%
“…A signal at d 179.8 in the 13 C NMR spectrum indicated the presence of acidic carbonyl function. Based on these data and those reported by Kawahara et al (2000) and Soulages et al (1994), we concluded that the isolated antifouling compound was 2-hydroxymyristic acid (HAB) (Fig. 1).…”
Section: Identification Of Antifouling Compoundssupporting
confidence: 70%
“…Previous in vitro studies showed that, in some model systems, apoLp-III binds to PC or other phospholipids (26,(32)(33)(34). However, apoLp-III does not bind to lipoprotein particles whose surface appears to be covered almost exclusively by phospholipid (4,35,36). The presence of DG on the lipoprotein surface seems to be necessary to trigger the binding of apoLp-III.…”
Section: Discussionmentioning
confidence: 98%
“…Insect Lps may function as reusable shuttles for lipid transport (Blacklock and Ryan, 1994;Soulages et al, 1994;Arrese et al, 2001;van der Horst et al, 2002). For example, Lp complexes transfer diacylglycerols to flight muscles and the protein can be recycled back to the hemolymph.…”
Section: Introductionmentioning
confidence: 99%